2022
DOI: 10.21037/atm-21-6251
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy related long non-coding RNA and breast cancer prognosis analysis and prognostic risk model establishment

Abstract: Background: The role of autophagy-related long-stranded non-coding RNA (lncRNA) in breast cancer (BRCA) is unclear. We proposed to screen autophagy-related lncRNAs in BRCA and construct a prognostic risk assessment model to explore prognostic correlates. Methods:We extracted BRCA lncRNAs from The Cancer Genome Atlas (TCGA) database and autophagy-related genes from the Human Autophagy Database (HADb), to screen for autophagy-related lncRNA pairs (ARLP) in BRCA. Single-factor Cox regression analysis and multi-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, additional investigations are need to confirm this hypothesis. Previous study indicated that CYTOR, [70] MIRLET7BHG, [71] SNHG17, [72] and MAPT-AS1 [73] were autophagy-related lncRNAs by Pearson’s correlation test. Autophagy has the ability to control FA metabolism, as evidenced by studies, [74,75] which is probably why these lnc RNAs were implicated in our ceRNA network connected to FA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional investigations are need to confirm this hypothesis. Previous study indicated that CYTOR, [70] MIRLET7BHG, [71] SNHG17, [72] and MAPT-AS1 [73] were autophagy-related lncRNAs by Pearson’s correlation test. Autophagy has the ability to control FA metabolism, as evidenced by studies, [74,75] which is probably why these lnc RNAs were implicated in our ceRNA network connected to FA metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Immune cell bubble plots showed that low-risk groups had higher levels of immune infiltration. It has been reported that the high immune infiltration state tends to have a better immunotherapeutic effect ( Guo et al, 2022 ; Luo et al, 2022 ). Interestingly, immune scores and immune checkpoint expression levels were also higher in the low-risk group, which is consistent with the results of Yu et al (2021) .…”
Section: Discussionmentioning
confidence: 99%
“…They are not generally considered to encode proteins but are involved in the regulation of different levels (epigenetic regulation, transcriptional regulation, and post-transcriptional regulation) of genes encoding proteins in the form of RNA ( Juhling et al, 2009 ; Spizzo et al, 2012 ). Several lncRNAs, including ferroptosis-related lncRNAs ( Chen et al, 2022 ), pyroptosis-related lncRNAs ( Xu et al, 2022 ), and autophagy-related lncRNAs ( Luo et al, 2022 ), have recently been implicated in prognosis in cancer patients, while m7G-related lncRNAs have rarely been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that LINC01871 may play a protective role in breast cancer. According to a recent review of the literature, LINC01871 has been identified by several studies in breast cancer through bioinformatic measurement involving the cellular phenotype of autophagy ( Li et al, 2021 ; Wu et al, 2021 ; Jiang et al, 2022 ; Luo et al, 2022 ), stemness ( Li et al, 2020 ), immune response ( Ma et al, 2020 ; Mathias et al, 2021 ), ferroptosis ( Xu et al, 2021 ), and lipid metabolism ( Shi et al, 2022 ). IGLC2 has a similar expression and functional pattern to LINC01871 in our study ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 99%